Evaluation of Learning Cycle 4E-RE to Improve Chemistry Learning of Vocational High School Student - Dinihari, Pancayani; Effendy, Effendy; Rahayu, Sri; Dasna, I Wayan (Journal of Technical Education and Training, 2021)
This study aimed to examine the effect of the Learning Cycle 4E-RE on the vocational school studentsâ€™ chemistry learning outcomes in light vehicle engine maintenance subject. The research subjects were 164 Vocational High School (SMK) students majoring in Technology and Engineering, the Automotive Engineering expertise program, consisting of 100 students in the experimental group and 64 students in the control group. The research instrument was a learning outcome test with 30 multiple-choice items with reliability of Kuder-Richardson Ï (KR 20) = 0.837. This study used a quasi-experimental pre / posttest control group design. The mean similarity of the experimental class and the control class was tested from the pretest results using t-test statistical analysis. The research hypothesis was tested using the ANCOVA test with a significance level of 5% (0.05). The results showed that there were differences in the learning outcomes of students who were taught with the Learning Cycle 4E-RE strategy with students who were taught with verification/conventional teaching. Student learning outcomes in the experimental class were higher than those in the control class. The implication of this research is that contextual learning strategies such as the Learning Cycle 4E-RE are suitable for vocational students to improve their learning outcomes. For further research, reflection activities in a learning strategy need to be tested again using different learning strategies and chemistry topics.